Estratégias de atendimento no comércio varejista para fidelização do cliente na cidade de Parintins/AM - Alfaia, Roberto dos Passos (Brasil, 2024)
One of the strongest points of sale in Brazil is retail trade, driving the economy broadly, especially in the supermarket sector, which plays a crucial role in the economy, both nationally and locally. Therefore, it is essential that these establishments seek effective customer loyalty strategies, which is a fundamental factor in ensuring the success and growth of retail in each city. Thus, the biggest problem in retail has to do with competition, where especially in small cities, retail entrepreneurs are involved in an environment that requires quick formulation of decisions that are part of the institutional environment. Given this scenario: Considering consumer satisfaction and the image of the Parintinian retailer, what have customer loyalty strategies been like in retail stores in the food sector? To answer this question, the study's general objective was to understand service strategies in retail trade to build customer loyalty, and to achieve the desired results, the following specific objectives were outlined: highlighting the strategies adopted by retail trade to build customer loyalty; identify the need for quality improvements in retail stores; and indicate strategies that favor retail trade based on the results achieved. It is justified that the research contributes significantly in order to demonstrate a reflective vision about the need to understand what good service consists of, and which strategies can help the retail sector to be efficient in building customer loyalty in the city. The content analysis of the quality management service and possible loyalty strategies for businesses in this qualitative descriptive research was carried out based on field research, where the main methods were a bibliographical review based on books, scientific articles, dissertations, among other materials and the application of a questionnaire in 3 companies in the retail sector in the food sector in the city of Parintins/AM. The main authors in the area used as the theoretical basis of the research were: Kotler and Keller (2018). The results inferred us to the knowledge of the most advantageous strategies of local companies to become a loyal and satisfied customer, such as promotion, discount and personalized service, in addition to showing the challenges with fierce competition and the lack of professionalism of employees. The importance was given to communicating with customers to publicize and verify customer attraction and retention.